Classification of Haplogroup C and Haplogroup D in Modern Malay and Chinese population of Peninsular Malaysia - Atan, Edinur Hisham (Universiti Sains Malaysia, 2006)
Mitochondrial DNA analysis is carried out for 45 samples from modem Malay and 44 samples from modem Chinese populations of Peninsula Malaysia. The mitochondrial DNA coding region variation of these samples was examined using restriction fragment length polymorphism (RFLP) method. From the analysis of Alu I site gain nucleotide position 10397, 37.78% of modem Malay population of peninsular Malaysia belongs to superhaplogroup M while 4 7. 73% of the modem Chinese belong to superhaplogroup M. Superhaplogroup M is further divided into several haplogroup, which are defined by the presence of specific RFLP markers. Haplogroup C and Haplogroup D are determined by the presence of Alu l restriction site at the nucleotide position 13 262 and the absence of Alu 1 restriction site at the nucleotide position 5 176. For Modem Malay population, only 8.89% of the sample belongs to the haplogroup D while none belong to the haplogroup C. For modem Chinese population of peninsular Malaysia, 4.65% of the samples belong to haplogroup C and 6.82% of the samples belong to the haplogroup D.